Does innovation spur integrated reporting? - Pinto, R.; Lourenço, I.; Ferreira, A. (Sustainability, 2023)
This study analyses whether country-level innovation performance and firm-level innovation commitment are associated to adopting the integrated reporting in Europe. The empirical analysis relies on a logistic regression model applied to 388 firm-year observations regarding firms located in Europe and data between 2016–2019. The results show a positive and significant association between country-level innovation performance and integrated reporting uptake. Moreover, at a firm- level, the data partially support that the influence of innovation commitment on the likeli-hood of publishing integrated reports is higher for firms with a higher-level of sustainability performance. This research contributes to the literature by focusing, simultaneously on the impact of country-level innovation performance and firm-level innovation commitment on integrated reporting acceptance in the European setting. In addition, the adopted country-level conceptual support is based on the institutional theory combined with the framework of the national inno-vation systems. The latter, to the best of our knowledge, has not yet been applied in this line of research